Autophagy in intestinal fibrosis: relevance in inflammatory bowel disease - Macias-Ceja, Dulce C.; Barrachina, María D.; Ortiz-Masià, Dolores (Frontiers in Pharmacology, 2023)
Chronic inflammation is often associated with fibrotic disorders where excessive deposition of extracellular matrix is the hallmark of many fibrotic diseases. Long-term fibrosis can lead to organ and tissue hypofunction and even functional failure. Intestinal fibrosis is not an exception, and it is a common and serious complication of the inflammatory bowel disease (IBDs). Several studies have confirmed a correlation between dysregulated autophagy and fibrotic diseases but, although the existence of shared prognostic markers, both up- and down-regulation of autophagy have been hypothesized to be involved in fibrosis progression. With a better understanding of the effects of autophagy on fibrosis, autophagy may have potential as a target of antifibrotic therapy. In this review we illustrate recent insights in the field, suggesting the possible implication of the autophagy in fibrosis, with special interest in fibrosis observed in IBD patients.